Association of brain-derived neurotrophic factor in blood and cerebrospinal fluid with Parkinson’s disease and non-motor symptoms of Parkinson’s disease: a systematic review and meta-analysis of 6655 participants - Zhao, Zhenzhen; Sun, Jiahui; Liu, Youhong; Liu, Miao; Tong, Di (Frontiers in Aging Neuroscience, 2025)
BackgroundBrain-derived neurotrophic factor (BDNF) is essential for regulating neuronal proliferation and survival in neurodegenerative diseases, including Parkinson’s disease (PD). However, Studies on BDNF levels in peripheral blood and cerebrospinal fluid (CSF) have inconsistent results. Therefore, this study aimed to examine BDNF levels in patients with PD and to explore their correlation with non-motor symptoms.MethodsFour databases (PubMed, Embase, Cochrane Library, and CNKI) were searched for eligible studies. The quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS). Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated using Stata version 14.0, applying either a fixed-effect or a random-effects model based on heterogeneity. Furthermore, subgroup analysis, meta-regression, and sensitivity analysis were employed to identify and analyze sources of heterogeneity. Publication bias was assessed using funnel plots and Egger’s test.ResultsA comprehensive systematic review and meta-analysis was conducted, encompassing 48 articles. A total of 38 studies, covering 2,589 patients with PD and 2,422 healthy controls, were analyzed, revealing significantly lower peripheral blood BDNF levels in PD patients compared to healthy controls (SMD = −1.037; 95% CI [−1.412, −0.662]; P < 0.001), with substantial heterogeneity (I2 = 97.0%; P < 0.001). This result may be more applicable to serum samples and the Asian population according to subgroup analysis. PD patients with depression showed no significant difference in serum BDNF levels compared to those without depression (SMD = −0.511; 95% CI [−1.692, 0.671]; P = 0.397). A significant association was found between decreased serum BDNF concentrations and cognitive impairment in PD (SMD = −1.035; 95% CI [−1.340, −0.730]; P < 0.001). Moreover, negative correlations were observed between lower serum BDNF levels and autonomic dysfunction, rapid eye movement sleep behavior disorder (RBD), and restless legs syndrome (RLS), respectively. However, CSF BDNF levels showed no statistically significant difference between PD patients and controls (SMD = −0.398; 95% CI [−2.499, 1.703]; P = 0.711).ConclusionReduced expression of BDNF is associated with both PD and its non-motor symptoms. Further research is needed to explore the potential of BDNF as a biomarker for non-motor symptoms of PD, particularly for cognitive impairment.